PENGARUH JUMLAH WAJIB PAJAK TERDAFTAR DAN PENERBITAN SURAT PAKSA TERHADAP PENERIMAAN PAJAK PENGHASILAN PADA KPP PRATAMA BANTUL - Nanik Fitriani (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2013)
This study aims to determine the effect of total and publishing Registered Taxpayers Forced letter of acceptance in the KPP Pratama Bantul Income Tax. Analysis used is multiple regression analysis. Before using multiple regression analysis, performed classical assumption test. Partial hypothesis test results (t-test) showed a variable amount of Registered Taxpayers positive and significant effect issue of forced variable has no effect on income tax receipts. Simultaneous hypothesis test results (F-test ) shows the number of Registered Taxpayers and variable force simultaneous issuance of a significant positive effect on income tax receipts. This study showed 35,1 % income tax receipts are affected by variable amounts Registered Taxpayers and issue of Forced and 64,9 % explained by other factors outside the discussion. Keyword: the number of registered taxpayers, issue of forced labor, withholding tax